Philip Morris vs. tobacco control: two wins for public health, but uncertainty remains - Tania Voon; Andrew D. Mitchell (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Two investment treaty claims launched by Philip Morris entities against tobacco control measures implemented by Australia and Uruguay have ended, with Philip Morris losing both disputes. This Perspective highlights these positive results from a public health viewpoint while emphasizing the continued need for reform of the investment regime.
Keywords: 330